2018
DOI: 10.1371/journal.pone.0201118
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end products (AGEs) estimated by skin autofluorescence are related with cardiovascular risk in renal transplant

Abstract: BackgroundAdvanced glycation end products (AGEs) accumulation, a measure of cumulative metabolic stress, constitute a novel pathogenic mechanism involved in aging, diabetes, cardiovascular (CVD) and chronic kidney disease (CKD). Despite removal of uremic toxins and AGEs after a successful renal transplant (RT), CVD remains the leading cause of mortality. We hypothesized that AGEs measurement by Skin Autofluorescence (SAF) might be useful even after a successful RT and thus reflect the high cardiovascular risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 51 publications
(69 reference statements)
2
21
1
Order By: Relevance
“…Furthermore, our analyses relied on data from direct and specific measurements of two major circulating AGEs. Of note, previous evidence has also been limited to the use of skin autofluorescence readings (10)(11)(12)(13). It is critical to take into account that the current understanding of AGEs a The coefficients of the indirect ab path and the total ab+c' path are standardized for the SD of the potential mediators, circulating CML and CEL concentrations and cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our analyses relied on data from direct and specific measurements of two major circulating AGEs. Of note, previous evidence has also been limited to the use of skin autofluorescence readings (10)(11)(12)(13). It is critical to take into account that the current understanding of AGEs a The coefficients of the indirect ab path and the total ab+c' path are standardized for the SD of the potential mediators, circulating CML and CEL concentrations and cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with ESKD, clinical studies have shown the adverse cardiovascular and survival effects of AGEs (10,11). In kidney transplant recipients, the hypothesis that AGEs play a role in the pathogenesis of cardiovascular disease may be supported by evidence that connects indirect and nonspecific measurements of AGEs with risk factors of cardiovascular disease (12,13). A strong body of evidence on the general theory of circulating AGE pathology supports its pivotal role in the initiation and progression of cardiovascular disease, which, in turn, is the leading individual cause of premature mortality after a successful kidney transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…The putative role of membrane RAGE activation and sRAGE circulating levels in cardiovascular complications of CKD patients are still very controversial. Previous studies indicated that AGEs levels are higher in CKD patients and, by interacting with membrane RAGE, they may activate intracellular signaling pathways that lead to oxidative stress, inflammation, vascular stiffness, atherosclerosis, tissue remodeling, and fibrosis [ 39 41 ]. Blockage of RAGE has been suggested as one potential protective mechanism against AGE-induced cardiovascular complications and sRAGE may just work in this way by linking to AGEs and preventing their interaction with RAGE [ 6 , 40 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In spontaneously hypertensive rats, the levels of AGEs were shown to be elevated [35]. Meanwhile, AGEs accumulation was shown to be closely related with night-systolic blood pressure, subclinical vascular atheromatosis and expected 10-year cardiovascular death risk in subjects with successful renal transplant [36]. In addition, chronic in ammation was recognized to be involved in the development of hypertension [37].…”
Section: Discussionmentioning
confidence: 99%